2017
DOI: 10.1002/jmri.25748
|View full text |Cite
|
Sign up to set email alerts
|

Cross‐sectional correlation between hepatic R2* and proton density fat fraction (PDFF) in children with hepatic steatosis

Abstract: 2 Technical Efficacy: Stage 1 J. Magn. Reson. Imaging 2018;47:418-424.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
25
3

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 21 publications
(30 citation statements)
references
References 38 publications
2
25
3
Order By: Relevance
“…We investigated whether R2* was associated with fat accumulation, which has previously been reported . Figure shows the correlation between R2* and PDFF, measured by MRS.…”
Section: Resultsmentioning
confidence: 76%
See 1 more Smart Citation
“…We investigated whether R2* was associated with fat accumulation, which has previously been reported . Figure shows the correlation between R2* and PDFF, measured by MRS.…”
Section: Resultsmentioning
confidence: 76%
“…Recently, both Mamidipalli et al and Bashir et al reported that fat accumulation in the liver correlates with a slight increase in liver R2*. Although the exact mechanism is unknown, Mamidipalli et al hypothesized that, similar to iron, hepatic fat droplets induce local susceptibility effects, leading to an increased R2*.…”
mentioning
confidence: 99%
“…The relationship between R2* and PDFF was examined using Pearson's correlation, since a linear relationship had been found in previous works . This analysis was repeated for the subset of subjects with and without hepatocellular or nonhepatocellular iron at each field strength, and Spearman's correlation was used if the relationship appeared nonlinear and/or numerous outliers were present .…”
Section: Methodsmentioning
confidence: 99%
“…To date, two retrospective single‐center studies by Bashir et al and Mamidipalli et al have independently shown that liver PDFF and R2* values are positively correlated in vivo at 3T magnetic resonance imaging (MRI) in populations without iron overload . Although limited by lack of histological correlation, these studies suggest that in patients without risk factors for severe iron overload (eg, patients with NAFLD), R2* may not be an unconfounded measure of liver iron.…”
mentioning
confidence: 99%
“…The linear term c 1 is compatible with the effects of susceptibility‐induced dephasing caused by the difference in magnetic susceptibility between water and fat. Previous studies have reported a positive correlation between PDFF and R 2 * with slopes of between 25 and ≈100 s −1 . R 2 * in these studies is a monoexponential approximation of the decay and therefore not directly comparable with c 1 .…”
Section: Discussionmentioning
confidence: 85%